Nanostore Supply Chain Performance: Meta-Analysis of Industry 4.0 and 5.0 Integration for Human-Centric and Sustainable Retail - Ortega-Jimenez, Cesar H; Paque Salazar, Ana Lucia; Ramírez Zarta, Jorge Bernardo; Melgar Martínez, Narciso A (LACCEI, 2025)
This study examines the impact of Industry 4.0 and Industry 5.0 technologies on nanostore supply chains through a meta-analysis of 52 recent studies. While prior research often centers on operational efficiency and inventory control, this study emphasizes the combined value of digitalization and human-centric, sustainable approaches. Industry 4.0 technologies—such as IoT, AI, and blockchain—demonstrate clear benefits in improving performance metrics, while Industry 5.0 enhances adaptability, resilience, and competitiveness in small-scale retail. A key contribution is the identification of how Industry 5.0 supports the transition toward customer-centric, sustainable models without compromising efficiency. The analysis also uncovers critical gaps in the literature, including limited research on implementation challenges at the micro-business level. Despite methodological variability, findings suggest the need for longitudinal studies, broader regional representation, and standardized research designs to ensure comparability. Practically, nanostores stand to gain from these technologies and policy support—through targeted funding, training, and partnerships—can accelerate adoption. This study contributes to the theoretical discourse on digital transformation in informal retail and offers actionable insights for enhancing nanostore performance while aligning with inclusive and sustainable development goals.